2022
DOI: 10.3390/molecules27134301
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Studies on Zinc Oxide Based Nanostructured Oil Carriers with Seed Extracts of Nigella sativa and Pimpinella anisum as Potential Inhibitors of 3CL Protease of SARS-CoV-2

Abstract: Coming into the second year of the pandemic, the acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its variants continue to be a serious health hazard globally. A surge in the omicron wave, despite the discovery of the vaccines, has shifted the attention of research towards the discovery and use of bioactive compounds, being potential inhibitors of the viral structural proteins. The present study aimed at the green synthesis of zinc oxide (ZnO) nanoparticles with seed extracts of Nigella sativa and Pim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…The overall RMSF values for the protein alone, as well as when it interacted with ligands, were in the range of 3.6 Å to 4.8 Å, with the exception of Zinc Oxide. These results are fairly similar to those obtained by Hendi and others [ 22 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The overall RMSF values for the protein alone, as well as when it interacted with ligands, were in the range of 3.6 Å to 4.8 Å, with the exception of Zinc Oxide. These results are fairly similar to those obtained by Hendi and others [ 22 ].…”
Section: Resultssupporting
confidence: 93%
“…The final ligand, meropenem, presented three hydrogen bonds with the residues LUS 21, GLY 117, and TRP 299. This indicates that these amino acid residues are necessary for target binding and that they exert activity [ 22 ]. A favorable and stable binding position of the compounds within the binding pocket of the target protein is indicated by extremely low energy scores [ 21 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All LCs were found to inhibit the adsorption of viruses to the host cell surface and disable them via induction of iNOS mRNA of cytokines including IL-1β and IL-10. Currently, seed extracts of P. anisum showed significant effects against the acute respiratory syndrome coronavirus 2 (SARS-CoV-2) considered a serious health hazard internationally [ 93 ]. Preparation of green synthesis combining zinc oxide nanoparticles, seed extracts of P. anisum and Nigella sativa loaded nanostructured oil carriers (NLC) (composed from black seed and olive essential oils) were extensively characterized (high docking energy scores (ranging from − 7.9 to − 9.9 kcal/mol) and tested against SARS-CoV-2 main protease (3CLpro or Mpro).…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Furthermore, several recent in silico studies have demonstrated by molecular docking analysis that Zn could have a strong affinity and inhibit the main cellular compound targets of SARS-CoV-2, including the angiotensin-converting enzyme 2 (ACE2) receptor (which could be considered the main entry target of the virus), RNA-dependent RNA polymerase (RdRp), and the main protease activities (3-chyomotrypsin-like protease (3CLpro), etc.) used for virus replication [ 47 , 48 , 49 , 50 ]. Interestingly, the results from recent in vitro studies have confirmed the findings from in silico screening and revealed that Zn alone or in conjugation with other compounds (Zn ionophore, drug, etc.)…”
Section: Zinc As An Immunomodulatory Element and Its Implications For...mentioning
confidence: 99%